RETRIBUSI PARKIR DAN RETRIBUSI PASAR DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH KABUPATEN SUMBAWA - Apriani, Fita; Kurniawansyah, K; Ismawati, I (Jurnal Ekonomi & Bisnis, 2025)
This study aims to know the effect of parking retribution and market retribution on District Own Source Revenue in Sumbawa district. The type of this study was associative study. The type data used in this study was quantitative data. The source of data in this study was secondary in the form of time series. The methods used to collect data were through interviews and documentation. The data analysis tool used was multiple linear regression and the data was processed using the SPPS application. The results of the study showed the regression equation Y= 1.764 + 54.30X1 – 15.032X2 + e. Parking Retribution (X1) did not have significant effect District Own Source Revenue (Y) in Sumbawa district it was based on the result of t-value was lower than t-table (1.177 < 2.353). Furthermore Market Retribution (X2) did not have significant effect on District Own Source Revenue (Y) in Sumbawa district, it was based the result of t-value was lower than t-table (1.480 < 2.353). Then parking retribution and market retribution did not have significant effect on District Own Source Revenue in Sumbawa district, it was based on the result of f-value was lower than f-table (1.421 < 9.55). The coefficient of determination or R-square was 0.144, thus the percentage effect of Parking retribution (X1) and Market retribution (X2) on District Own Source Revenue (Y) in Sumbawa district was 14.4%, while 85.6% was affected by other variables were not studied, such as population, local taxes, inflation, and number of tourist visits.